PERAN ORANG TUA DALAM PENDAMPINGAN BELAJAR AGAMA ISLAM ANAK PADA MASA PANDEMI COVID 19 (Studi Kasus Di Kampung Nelayan Desa Mentoso Tahun 2021) - Siti Nurjanah; Rani Fatmawati (PREMIERE : Journal of Islamic Elementary Education, 2021)
Learning mentoring is an effort to accompany, accompany, motivate, facilitate, and supervise children in the learning process (Dwi, 2018). It is hoped that this mentoring program can help overcome the obstacles faced in the implementation of online training during the Covid19 pandemic by optimizing the role of mentoring in the world of education. Therefore, the objectives of this study are 1) to identify the obstacles faced by elementary school students in the fishing environment of Mentoso village during the COVID-19 pandemic and 2) to clarify the role of mentoring programs in learning in students' understanding. Based on the research, it can be concluded that the learning assistance for Islamic Religious Education for children in Ds. Mentoso with the educational limits of parents is indeed influential, but it returns to the characteristics of children and the ability of parents to persuade and overcome situations. Time constraints can be overcome by registering children with the tutor. it does add to the burden but this learning mentoring also results in good relationships between individuals and parents, increases closeness, can monitor children's character and children's academic abilities improve well. It can also be seen the attention given by parents to their children. Parents are also trained to continue to motivate children so that children can trigger enthusiasm and produce optimal achievements.